Implementasi Manajemen Kesiswaan Dalam Meningkatkan Kedisiplinan Siswa Kelas VIII MTs Al Falah Kecamatan Tapos Kota Depok - Ambami, Neneng Syaripah; Islamiati, Siti Hadiyati Dini; Riyadi, Ahmad (Transformasi Manageria Journal of Islamic Education Management, 2024)
2, Ahmad Riyadi31,2,3IAIN Laa Roiba Bogornenengsyarifah09@gmail.com1, dinihadirachman@gmail.com2, adom.rama@gmail.com3 ABSTRACTStudent discipline is a rule that always exists in the educational environment, disciplinary attitude is a mandatory attitude and must be possessed by every individual, especially schools. School is one of the educational environments after family education that must pay attention to student discipline in participating in the learning process, because it needs cooperation between parents, principals and teachers in improving student discipline. By increasing the attitude of discipline, management is also needed, the management needed is student management which regulates student activities at school and also plays a role in increasing student discipline. The implementation of management in schools certainly plays a very important role in an activity that is carried out effectively and efficiently to improve school performance in achieving educational goals. in this research conducted at MTs Al Falah, Tapos District, Depok City, which is an institution that supports students to live a disciplined life. The method used in this research is descriptive qualitative research. Data collection techniques are interviews, observation, and documentation. In this study, the subject were school princhipals, class VIII teachers, vice principals and guidance and counseling teachers.The results of the study show that the implementation of student management in improving student discipline has been carried out well. However, the attitude of discipline must be further enhanced by imposing penalties or sanctions for those who violate it, and student management must be able to manage students more effectively Keywords: discipline, student management.